PENGARUH LATIHAN LADDER DRILLS TERHADAP PENINGKATAN KELINCAHAN SISWA U-17 DI PERSATUAN SEPAKBOLA JAJAG KABUPATEN BANYUWANGI - Firdaus Soffan Hadi; Eko Hariyanto; Fahrial Amiq (Fakultas Ilmu Keolahragaan UM)
Abstract: Football is a game which played by 2 groups that try to shoot the ball to the other team’s goal posts using the whole body except hands, and the team that shoot more ball will be out as the winner. Physical condition is crucially important in Football. Technique and tactic errors often occur when players play with less portion of exercises. One of several ways to improve the skills of those players is by using ladder drills exercise. The better the agility of a player, the better the player apply them on the match. This research aims to know if the ladder drills training has an effect to increase Football players’ ability in agility of U-17 soccer players in Perseja Jajag Banyuwangi Football Association. Do ladder drills for exercise (mean = 20,03 dan SD = 1,63) gives better effect to increase U-17 soccer players in Perseja Jajag Banyuwangi Football Association agility ability than do the command exercise (mean = 26,30 dan SD = 2,16). Thus, ladder drills gave better effect than conventional exercise to increase agility capabilities of U-17 Football players in Jajag Banyuwangi Football Association.Keywords: football, ladder drills, exercise, and agility.Abstrak: Sepakbola adalah permainan yang dimainkan oleh dua regu yang saling berusaha memasukkan bola ke gawang lawan dengan menggunakan seluruh anggota badan kecuali tangan dan bagi tim yang lebih banyak memasukkan bola akan keluar menjadi juara. Salah satu komponen kondisi fisik yaitu daya tahan /stamina yang dapat dilihat kelincahan pergerakan pemain. Tujuan penelitian ini adalah untuk mengetahui ada tidaknya pengaruh latihan ladder drills terhadap peningkatan kelincahanpemain Persatuan Sepakbola Jajag Kabupaten Banyuwangi. Latihan ladder drills (mean = 20,03 dan SD = 1,63) memberikan pengaruh lebih baik terhadap peningkatan kemampuan kelincahan pemain sepakbola Jajag Kabupaten Banyuwangi daripada latihan konvensional (mean = 26,30 dan SD = 2,16). Latihan ladder drills memberikan pengaruh yang lebih baik dibandingkan latihan konvensional terhadap peningkatan kelincahanpemain sepakbola U-17 di Persatuan Sepakbola Jajag Kabupaten Banyuwangi.Kata kunci: sepakbola, latihan, ladder drills, dan kelincahan.